Kontexty výskumu kultúrno-kreatívnych centier na Slovensku - Winkler, Tomáš (Lidé města, 2021)
Cultural and creative centres are a relatively new phenomenon in the urban environment of Slovakia. Local and state politicians, as well as experts, often automatically link their functioning with the popular urban development concept of creative cities, focusing on the fields of creative economy and creative industries and emphasizing the economic effect of these centres. My qualitative research of the cultural and creative centre Nová Cvernovka in Bratislava showed the thematic diversity of such places in Slovakia and their significant impact on the topics of urban social movements, civic activism, transactional activism, and eventization. Thus, cultural and creative centres are fertile ground (also) for qualitative research in the social sciences. For this reason, a more precise definition of the term and clarification of this scientific concept are needed. The aim of the presented empirical study is to contribute to the definition of cultural and creative centres in Slovakia and to draw attention to several possible areas of their impact on the urban and social environment.